Plan de implementación de un sistema de gestión de la calidad e inocuidad alimentaria en una empresa de alimentos deshidratados basado en la FFSC 22000 (2020)
FOODSACOL is a dehydrated food company that is located in the city of Bogotá, it is currently producing dehydrated fruit to be marketed under the Manyare brand, in the presentation of a 30gr package of mango, banana and pineapple fruit mix, a product which is 100% natural, the company seeks to enter in the food industry with a quality product in the healthy food sector. This monograph aims to establish an implementation plan for the food safety and quality management system, based on the international standard FSSC 22000. Initially, an analysis of the internal and external issues of the company is carried out by the five PORTER forces, PESTELE analysis, and VRIO model. The analysis is consolidated in a DOFA matrix and the strategies for the case study company are established. Subsequently, with the first steps of the HACCP system, the dangers are identified and the risks of the production process are assessed. Finally, an activity plan is established based on the diagnosis of the current state of compliance of the company concerning the requirements of the FSSC 22000 standard. This document constitutes a work plan for the implementation of the international standard, and in the future achieves the certification, as well as guaranteeing the quality and safety necessary for the processes of commercialization and export of the products.